The great unknown: Japanese American sketches - Robinson, Greg, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
Introduces a readable collection of portraits about a group of extraordinary men and women who made remarkable contributions in the arts, literature, law, sports, and other fields, and shed light on largely unknown aspects of Japanese American history.--Provided by publisher. An anthology of articles that originally appeared in the column, "The Great Unknown and the Unknown Great," in the Nichi Bei Times and the Nichi Bei Weekly, and several articles that appeared in other periodicals, as well as some previously unpublished material.
Issei women: an overview -- Shio Sakanishi, Library of Congress official and scholar -- Fuki Endow Kawaguchi's diary -- Tel Sono, Issei women lawyer and missionary -- Ayako Ishigaki, feminist and peace activist -- Isamu Noguchi's struggle against executive order 9066 -- Kathleen Tamagawa, first Nisei author -- The Chino and Ohi families -- Milton Ozaki, mystery writer -- Yone U. Stafford, pacifist militant -- Jenichiro Oyabe, a "Japanese Yankee" at Howard University -- Eddie Shimano, crusading journalist and poet -- Kay Karl Endow, novelist, aviator, and con man -- John M. Maki, writer and educator -- Bill Hosokawa and Buddy Uno: Nisei journalists in occupied China -- The hidden contributions of Guyo Tajiri -- The tragic and engaging career of Sam Hohri -- Hisaye Yamamoto and the African-American press -- Mitsuye Endo-plus grand dans son obscuritø? -- Lincoln Seiichi Kanai's act of conscience -- The exclusion of Naomi Nakano -- Koji Ariyoshi, a Hawaiian Nisei in Mao's china -- Sanji Abe and martial law in wartime Hawai'i -- The McCloy memo: new insight into the causes of removal -- Norman Thomas and the defense of Japanese Americans -- Paul Robeson: "your fight is your my fight " -- Alan Cranston and Japanese Americans -- Two wartime governors and mass removal -- Hugh Macbeth, African American defender of Issei and Nisei -- John Franklin Carter: the real-life Lanny Budd -- Masuji Miyakawa, first Issei attorney -- The family behind Oyama v. California -- Regan v. King: when birthright citizenship was last tested -- Yasuo Sasaki, poet, physician and abortion rights pioneer -- Ina Sugihara, interracial activist -- Mervyn Dymally: unsung hero of Japanese American redress -- Setsuko M. Nishi, a life of service -- Arthur Matsu, first Japanese American in the National Football League -- Nisei in pro basketball: Wat Misaka and Dr. Yanagi -- Early Japanese Americans in organized baseball -- The Jacl and the integration of the American Bowling Congress -- Jun Fujita, poet and photographer -- Robert Kuwahara, cartoonist -- The double life of Conrad Yama -- Reiko Sato, actress -- The unknown life and art of Minø Okubo -- Gyo Fujikawa, artist and author -- Shinkichi Tajiri, sculptor -- Kiyoshi Kuromiya: a queer activist for civil rights -- Sexuality from Issei to Nisei -- The rise of homophobia in Japanese American Communities -- The rise of homophobia, part II -- Hawaii 1986: the shift to equal rights -- The Jacl's historic marriage resolution -- Japanese Americans in Louisiana -- Japanese Americans in prewar Chicago -- Japanese Americans and the death penalty -- The other side of the Hood River story -- S.I. Hayakawa, jazz specialist and civil rights supporter -- Anne Reeploeg Fisher and Morton Grodzins: the censorship of confinement -- Gordon Hirabayashi's surprising postwar career.
Keywords: Japanese Americans -- United States -- Biography; Japanese Americans -- United States -- History